Emergency Action Plan for Public Safety Around the Juaseh Dam, Johor - Said N.F.M.; Mohd Sidek L.; Mustafa Z.; Mansor F.H.; Jamal M.B. (Springer, 2023)
There are 104 dams in Malaysia for various functions and some of these dams have been built for more than 50 years ago. Among them, about 41 dams are classified as high-risk dams. Although, there are no dam failure cases in Malaysia reported dam failures to continue to occur worldwide and it is accepted a practice that dams must have an Emergency Action Plan (EAP) for management of disasters. An Emergency Action Plan, or EAP, is a formal plan that identifies potential emergency conditions at a dam and prescribes the procedures to be followed to minimize property damage and loss of life. As a dam owner responsibility, Badan Kawal Selia Air Negeri Johor (BAKAJ) initiated to develop EAP for Juaseh Dam in Johor, owned by the BAKAJ and operated by Syarikat Air Johor (SAJ). An emergency in terms of dam operation is defined as a condition, which develops unexpectedly, endangers the structural integrity of the dam and/or downstream property and human life and requires an immediate response. Developing an effective EAP requires communication and coordination between various groups including agencies and the local community. This paper presented the procedure of EAP preparation and components of EAP. The purpose and notification flowchart that summarizes the emergencies considered with the person in charge is included in this paper. In addition, the guideline of roles and responsibilities of the dam personnel, procedures for the timely and reliable identification, evaluation and classification of existing or potential emergency conditions, communication procedures, inundation maps and preventive action to prepare for any emergency is described in this research. 2020, Springer Nature Singapore Pte Ltd.